Fermentation : effects on food properties - Iwanski, Robert Z.; Kamal-Eldin, Afaf; Mehta, Bhavbhuti M. (Chemical and functional properties of food components series, 2012)
A large variety of food products all over the world are prepared by the fermentation of various raw materials. Fermentation: Effects on Food Properties explores the role of fermentation reactions in the chemical, functional, and sensory properties of food components as well as their effect on food component content and biological activity.Emphasizing the various chemical changes that take place during processing, both pre- and post-fermentation, the book explores: The complex microbial community in fermented foods The generation of the flavor and aroma compounds in fermented foods The effect o.